b - D. K. Bharadvaj; Sachitha (Gadaga B. G. S. Publications, 2024)
Vocabulary, Language, Technical Terminology, World General Knowledge.
Kannada
Keywords: Bharadvaj Dictionary; Kannada-English Dictionary; Standard Dictionary